The synergistic effects of soil-applied boron and foliar-applied silicon on cotton fiber quality and yield - Priscilla Maria da Silva Liber Lopes; Cid Naudi Silva Campos; Paulo Eduardo Teodoro; Milton Garcia Costa; Jonas Pereira de Souza Júnior; Renato de Mello Prado (BMC Plant Biology, 2023)
Abstract Studies of boron (B) and silicon (Si) synergy in cotton crops have shown promising results; however, the focus was on the foliar application of B and Si. Nonetheless, B is an element with little mobility in the plant and its best form of application is in the soil. Thus, the objective of this study was to evaluate the synergistic effect of soil applied B and foliar applied sSi on fiber quality and crop yield of cotton. For this purpose, a field experiment was carried out using cotton cultivar FM 985 GLTP. The soil’s B in the experimental site is classified as low for cotton cultivation. The experiment was conducted in a randomized complete-block design, in a 3 × 2 factorial scheme, with three doses of B: 0.0 kg ha−1 (deficiency), 2.0 kg ha−1 (recommended dose), and 4.0 kg ha−1 (high dose) in the absence and presence (920 g L−1) of Si, with four replications. One week after the 4th application of Si, B and Si leaf content was determined. At boll opening, crop yield was estimated, and fiber quality analysis was realized. Boron deficiency reduced cotton yield, in 11 and 9%, compared to the application of 2 and 4 kg ha−1 of B, respectively. The presence of Si, however, increased plant yield in 5% in the treatments with 0 and 2 kg ha−1 of B, respectively. Cotton fiber length and elongation were not influenced by the B doses and Si presence. Fiber breaking strength was increased in 5% by the presence of Si and was not influenced by B deficiency. Micronaire was 8% smaller in the treatment with 0 kg ha−1 of B and 6% smaller in the absence of Si. Short fiber index was 4% greater in the plants of the treatment with 0 kg ha−1 of B. The results of this study reports that the complementation with Si via foliar application increases fiber quality by enhance breaking strength and micronaire. In conclusion, the interaction between soil-applied B and foliar-applied Si is beneficial for cotton cultivation, resulting in high cotton yield with better fiber quality.